2021
DOI: 10.1038/s42003-021-02136-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevating CDCA3 levels in non-small cell lung cancer enhances sensitivity to platinum-based chemotherapy

Abstract: Platinum-based chemotherapy remains the cornerstone of treatment for most non-small cell lung cancer (NSCLC) cases either as maintenance therapy or in combination with immunotherapy. However, resistance remains a primary issue. Our findings point to the possibility of exploiting levels of cell division cycle associated protein-3 (CDCA3) to improve response of NSCLC tumours to therapy. We demonstrate that in patients and in vitro analyses, CDCA3 levels correlate with measures of genome instability and platinum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 59 publications
(59 reference statements)
2
23
0
Order By: Relevance
“…Given we have previously demonstrated that CDCA3 strongly correlates with platinum-based chemotherapy response in all NSCLC histologies [ 25 ], we next sought to determine whether a similar trend might exist with the response to EGFR TKIs. We evaluated TCGA datasets and correlated relative CDCA3 expression against available WikiPathways [ 31 ] of known measures of TKI resistance.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given we have previously demonstrated that CDCA3 strongly correlates with platinum-based chemotherapy response in all NSCLC histologies [ 25 ], we next sought to determine whether a similar trend might exist with the response to EGFR TKIs. We evaluated TCGA datasets and correlated relative CDCA3 expression against available WikiPathways [ 31 ] of known measures of TKI resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Lipofectamine RNAimax (Life Technologies) was used to transfect previously validated [ 24 ] negative control Stealth siRNAs and Stealth siRNAs (siCDCA3-1, sense 5′-ACUGGUGAAACAGCUGAGUGAAGUA-3′, anti-sense 5′-UACUUCACUCAGCUGUUUCACCAGU-3′) to deplete CDCA3 levels (ThermoFisher Scientific). Transfection of CDCA3-FLAG expression construct [ 25 ] was performed using the FuGene HD transfection reagent (Promega Corporation, Annandale, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations